ANALISIS AKUNTANSI PAJAK PENGHASILAN (PPh) PASAL 22 ATAS KEGIATAN IMPOR BARANG - Reivaldo Roel; Frida Magda Sumual; Aprili Bacilus (Universitas Methodist Indonesia, 2023)
This study plans to figure out how the estimation and revealing of products import exercises at the Manado Customs and Extract Oversight and Administration Office are as per the Law on Pastor of Money Guideline No. 41/PMK.010/2022 and furthermore to figure out the recording of Personal Expense Article 22 on merchandise import exercises. . The insightful technique utilized is an unmistakable strategy, specifically by gathering information, ordering, then, at that point, deciphering and breaking down it by going back over the information got to give a total depiction. The aftereffects of the exploration led, the computation and announcing of PPh Article 22 on merchandise import exercises at the Manado Customs and Extract Oversight and Administration Office are as per Clergyman of Money Guideline No. 41/PMK.010/2022. The Directorate General of Customs and Extract has carried out PMK No 41/PMK.010/2022 dated April 1, 2022 which has been recorded in Article II of PMK number 41/PMK.010/2022, to this guideline beginning April 1, 2022 all imported merchandise that are remembered for the classification of Article 22 Import Annual Expense gathered has followed how much Article 22 Personal Duty assortment as per the PMK.